Calculation of Consumption and Expenditures for Electricity Energy Costs at Lido Graha Hotel Lhokseumawe City Based on Electrical Power Measurement - Arnawan Hasibuan; Widyana Verawaty Siregar; Elvy Sahnur Nasution; Rohana Ismail (Bulletin of Computer Science and Electrical Engineering, 2020)
Evaluation of energy utilization and identification become energy saving opportunities, as well as recommendations for increasing efficiency, on energy use and use of energy sources in the context of energy conservation This paper aims to describe the audit of electrical energy in the Lido Graha Lhokseumawe Hotel room, by taking samples in different room types and conducting an electrical energy audit on the use of installed lights and air conditioners. The method used in this study is data collection, interviews, observations and direct measurements on the use of lights and AC (Air Conditioning). The data analysis technique used is to determine the estimated value of electricity consumption and how much it will cost for electricity. From the results of calculations and analysis obtained total electricity consumption needs based on the type of room with various types of loads used 855.62 kWh/days with costs that must be spent per day is Rp. 1,190,574.96, 25,668.6 kWh/month with a monthly cost of Rp. 35,087,608.60. Whereas for a year electricity demand is 308,494.8 kWh/year with a cost of Rp. 421,051,305.24.